![{sin}^{2}(51 - x) + {sin}^{2} (39 + x) = {sin}^{2}(51 - x) + {sin}^{2} (39 + x) =](https://tex.z-dn.net/?f=+%7Bsin%7D%5E%7B2%7D%2851+-+x%29+%2B++%7Bsin%7D%5E%7B2%7D+%2839+%2B+x%29+%3D++)
Answers
Answered by
2
Answer:
sin²(51-x)+sin²(39+x)
=sin(51)+sin(39+0)
=0.670229+sin(39+0)
=0.670229+sin(39)
=0.670229+0.963795
=1.634025
Answered by
5
Hii
you are welcome in my and
sin^2(51- X ) + sin^2 (39+X)
sin^2 (51 - X) + sin^2(90 - (51 -x))
sin^2 (51 - X) + cos^2(51 - X)
1
since
sin^2A + cis^2B = 1
_____/\___☺️
Hope it may helps you✊✌️
Similar questions